Dating buildings and landscapes with tree-ring analysis : an introduction with case studies - Rubino, Darrin L.; Baas, Christopher (New York, NY : Routledge, 2019)
This book presents guidance, theory, methodologies, and case studies for analyzing tree rings to accurately date and interpret historic buildings and landscapes. Written by two long-time practitioners in the field of dendrochronology, the research is grounded in the fieldwork data of approximately 200 structures and landscapes. By scientifically analyzing the tree rings of historic timbers, preservationists can obtain valuable information about construction dates, interpret the evolution of landscapes and buildings over time, identify species and provenance, and gain insight into the species matrix of local forests. Authors Darrin L. Rubino and Christopher Baas demonstrate, through full-color illustrated case studies and methodologies, how this information can be used to interpret the history of buildings and landscapes and assist preservation decision-making. Over 1,000 samples obtained from more than 40 buildings, including high style houses, vernacular log houses, and timber frame barns, are reported. This book will be particularly relevant for students, instructors, and professional readers interested in historic preservation, cultural landscapes, museum studies, archaeology, and dendrochronology globally.
6.14 Historic aerial photographs6.15 Secondary sources; 6.16 Conclusion; 6.17 Literature cited; 7 Reporting the results of tree-ring analysis; 7.1 Introduction; 7.2 Parts of a tree-ring analysis report; 7.3 Data tables; 7.3.1 Tree-ring sample table construction; 7.3.2 Outer rings and assigning construction dates; 7.3.3 Timbers without dates; 7.3.4 Chronology summary table construction; 7.4 Chronology and sample depth reporting; 7.5 Field drawings; 7.5.1 Field documentation of barns; 7.5.2 Field documentation of houses, churches, and commercial buildings; 7.6 Equipment for field documentation
OCLC-licensed vendor bibliographic record.
Keywords: Dendrochronology; Landscape archaeology; Archaeological dating; Historic buildings -- Dating; ARCHITECTURE / General; ARCHITECTURE / Landscape; ARCHITECTURE / Historic Preservation